2022
DOI: 10.1101/2022.09.19.507309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure tomycobacteriumremodels alveolar macrophages and the early innate response toMycobacterium tuberculosisinfection

Abstract: As innate sentinels in the lung, alveolar macrophages (AMs) play a critical role during Mycobacterium tuberculosis (Mtb) infection as the first cells to encounter bacteria. We previously showed that AMs initially respond to Mtb infection in vivo by mounting a cell-protective, rather than pro-inflammatory response, yet whether the AM response could be modified by environmental factors was unknown. Here, we characterize how previous exposure to mycobacteria, either through subcutaneous vaccination with Mycobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 77 publications
3
7
0
Order By: Relevance
“…Even prior to aerosol infection, there were differences in pathways associated with cell cycle and mitochondrial respiration in ILC2s in the setting of CoMtb, but not primary infection, potentially indicating innate training, which is consistent with previous reports (Fig 3A). 27 In agreement with our cellular abundance analysis, a stronger cell cycle/division response was seen in CD4 T cells following CoMtb at d17, indicating ongoing cellular activation and proliferation of T cells within the lung parenchyma. Starting d17 p.i., we also observed striking response differences in interferon response pathways which were upregulated over time across most cell populations (Fig 3A ).…”
Section: Comtb Accelerates T Cell and MDC Activation Blunts Neutrophi...supporting
confidence: 90%
“…Even prior to aerosol infection, there were differences in pathways associated with cell cycle and mitochondrial respiration in ILC2s in the setting of CoMtb, but not primary infection, potentially indicating innate training, which is consistent with previous reports (Fig 3A). 27 In agreement with our cellular abundance analysis, a stronger cell cycle/division response was seen in CD4 T cells following CoMtb at d17, indicating ongoing cellular activation and proliferation of T cells within the lung parenchyma. Starting d17 p.i., we also observed striking response differences in interferon response pathways which were upregulated over time across most cell populations (Fig 3A ).…”
Section: Comtb Accelerates T Cell and MDC Activation Blunts Neutrophi...supporting
confidence: 90%
“…However, our findings that resident alveolar macrophages in BCG vaccinated hosts display heightened phagocytic and killing capacities indicate that cutaneous BCG vaccination can also remotely impact the functionality of resident AMs. This observation is further supported by a recent study that showed cutaneous BCG vaccination in mice modifies the phenotype of alveolar macrophages in the airways and alters the in vivo alveolar macrophage responses to M. tb infection (28). An ongoing study in our laboratory also demonstrated that s.c BCG vaccination induces memory AMs with the characteristics of TII which goes on to provide enhanced early protection against M. tb infection (unpublished).…”
Section: Discussionsupporting
confidence: 61%
“…The current study provides further evidence that such TII in the lung following cutaneous BCG vaccination can also mediate heterologous protection against pulmonary S. pneumoniae infection. Interestingly, despite phenotypic and functional alterations in alveolar macrophages, gross cellularity in the airways is unaffected following cutaneous BCG vaccination, indicating that induction of TII in alveolar macrophages is independent of centrally trained monocytes (28, 29). Of note, although pulmonary S. pneumoniae infection led to the recruitment of centrally trained monocytes to the lung in BCG vaccinated hosts, they did not contribute to the enhanced protection as indicated by comparable clinical outcomes and bacterial control in BCG vaccinated CCR2 -/- and WT mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our findings that lung-resident AMs in s.c. BCG-vaccinated hosts display heightened phagocytic and killing capacities and protect against S. pneumoniae independent of circulating monocytes indicates that cutaneous BCG vaccination can also remotely impact tissue-resident AMs. This observation is further supported by a recent study that showed cutaneous BCG vaccination in mice remodels AMs in the airways and alters AM responses to M. tb infection via mediating a robust and dominant interferon response (preprint: Mai et al, 2022). Such altered functionality of AMs was long-lasting as indicated by comparable or even elevated enhanced responses to secondary ex vivo stimulation at 23 weeks compared to 8 weeks post-s.c. BCG vaccination.…”
Section: Discussionsupporting
confidence: 59%